Catalase-conjugated surfaces: H2O2 detection based on quenching of tryptophan fluorescence on conducting polymers. (5th January 2021) - Gelen, Sultan Sacide; Munkhbat, Tuvshinjargal; Rexhepi, Zuale; Kirbay, Fatma Ozturk; Azak, Hacer; Demirkol, Dilek Odaci
Graphical abstract: Highlights: A novel fluorescence tryptophan sequestered dithione [3, 2-b:2′, 3′-d] pyrrole (DTP-Trp) was synthesized. Dithione [3, 2-b:2′, 3′-d] pyrrole (DTP-Trp) was used as an immobilization support for catalase. H2 O2 detection was performed based on quenching of Trp fluorescence. P(DTP-Trp)/CAT improved performance parameters of H2 O2 sensing. Abstract: Conducting polymers are promising materials used to prepare electrochemical and optical detection platforms for bioanalytical systems. After conjugation of biomolecules onto electropolymerized monomers for preparation of multifunctional surfaces, they can be used to easily monitor small molecules, macromolecules, and cells. In this study, multifunctional monomer with indole (necessary for fluorescence detection of H2 O2 ) and carboxyl functional groups (necessary for covalent immobilization of biological material) was synthesized, electropolymerized, modified with biomolecules (catalase) and then applied for the selective detection of target analyte (H2 O2 ). Tryptophan sequestered dithione [3, 2-b:2′, 3′-d] pyrrole (DTP-Trp) was synthesized and electropolymerized on indium tin oxide (ITO) coated polyethylene terephthalate (PET) substrates, which is a transparent support. Afterward, catalase (CAT) was immobilized on the Poly(DTP-Trp) using a zero-length crosslinker, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), via covalent bonds between carboxyl groups of CAT and amino groups of Poly(DTP-Trp). Surface characterization of Poly(DTP-Trp)/CAT was done by scanning electron microscopy (SEM) and energy dispersive x-ray analysis (EDX). The presence of Poly(DTP-Trp)/CAT on ITO-PET surfaces were also confirmed by electrochemical methods to show the success of support modification. Determination of H2 O2 was investigated using fluorescence spectrometry based on quenching mechanism of H2 O2 on the fluorescence of tryptophan. After optimization of working conditions of Poly(DTP-Trp)/CAT, H2 O2 detection in synthetic samples was done without any interference of the matrices.